2022
DOI: 10.3847/2041-8213/ac86c3
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Winds and Bubbles from Nuclear Starburst Rings

Abstract: Galactic outflows from local starburst galaxies typically exhibit a layered geometry, with cool 104 K flow sheathing a hotter 107 K, cylindrically collimated, X-ray-emitting plasma. Here we argue that winds driven by energy injection in a ring-like geometry can produce this distinctive large-scale multiphase morphology. The ring configuration is motivated by the observation that massive young star clusters are often distributed in a ring at the host galaxy’s inner Lindblad resonance, where larger-scale spiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In NGC 253, the super star clusters within the nuclear core are likely arranged in a ring-like geometry (Levy et al 2022). Nguyen & Thompson (2022) recently showed that energy and mass injection in a ring-like geometry naturally produces a biconical outflow, where the hot phase is cylindrically collimated. When we include the effect of nonspherical flow geometry into the wind model (red and blue lines in Figure 6), we find better agreement with the profiles.…”
Section: Comparison To Wind Modelsmentioning
confidence: 99%
“…In NGC 253, the super star clusters within the nuclear core are likely arranged in a ring-like geometry (Levy et al 2022). Nguyen & Thompson (2022) recently showed that energy and mass injection in a ring-like geometry naturally produces a biconical outflow, where the hot phase is cylindrically collimated. When we include the effect of nonspherical flow geometry into the wind model (red and blue lines in Figure 6), we find better agreement with the profiles.…”
Section: Comparison To Wind Modelsmentioning
confidence: 99%
“…This may lead to the γ-ray bubble discovered by Fermi observations in the Milky Way (Su et al 2010). Other possible origins of the γ-ray bubble might be originally contributed by a starburst ring (Nguyen & Thompson 2022) or by a relativistic jet (Guo & Mathews 2012). The present model to the GC should be ).…”
Section: Supernovae Explosion: Support Dusty Torusmentioning
confidence: 96%
“…YMCs as potential drivers of large-scale gas outflows. Central starburst rings are believed to be powerful drivers of multiphase galactic winds and outflows (e.g., Armillotta et al 2019;Nguyen & Thompson 2022), and there are indications of such outflows from NGC 3351ʼs central ring from existing multiwavelength observations. By analyzing Chandra X-ray imaging data, Swartz et al (2006) found evidence of hot gas expanding beyond the starburst ring and likely above the plane of the galaxy.…”
Section: Ymcs In Large-scale Contextmentioning
confidence: 99%